Research progress on the relationship between gut microbiota and ferroptosis after ischemic stroke - PEI Xinyu; WU Minmin; ZHU Luwen (Yixue xinzhi zazhi)
Ischemic stroke (IS) is a clinical syndrome in which limited or total brain dysfunction is caused by cerebrovascular lesions and lasts more than 24 hours or causes death. Ferroptosis, a regulatory form of cell death dominated by iron accumulation and lipid peroxidation, is thought to be involved in the pathogenesis of IS. The occurrence of IS causes organ dysfunction. The effects on the gastrointestinal system lie mainly in the two-way communication between the intestine and the brain, involving the brain, gut microbiota and intestinal tissue, and it has been considered to be a key component of IS prognosis. This article takes ferroptosis as the main idea to discuss the research progress of the effect of gut microbiota on ferroptosis after IS, which provides a theoretical basis for the treatment and prevention of IS from the aspects of intestinal microbiota and ferroptosis mechanism.